Upregulation of Nogo‐B by hypoxia inducible factor‐1 and activator protein‐1 in hepatocellular carcinoma. Issue 7 (21st May 2021) - Han, Dingding; Yang, Penggao; Qin, Bo; Ji, Guoqing; Wu, Yanhua; Yu, Long; Zhang, Hong
Abstract: Nogo‐B is an important regulator of tumor angiogenesis. Expression of Nogo‐B is remarkably upregulated in multiple tumor types, especially hepatocellular carcinoma (HCC). Here, we show the transcriptional regulation mechanisms of Nogo‐B in liver cancer. In response to hypoxia, expression of Nogo‐B significantly increased in HCC tissues and cells. The distal hypoxia‐responsive element in the promoter was essential for transcriptional activation of Nogo‐B under hypoxic conditions, which is the specific site for hypoxia inducible factor‐1α (HIF‐1α) binding. In addition, Nogo‐B expression was associated with c‐Fos expression in HCC tissues. Nogo‐B expression was induced by c‐Fos, yet inhibited by a dominant negative mutant A‐Fos. Deletion and mutation analysis of the predicted activator protein‐1 binding sites revealed that functional element mediated the induction of Nogo‐B promoter activity, which was confirmed by ChIP. These results indicate that HIF‐1α and c‐Fos induce the expression of Nogo‐B depending on tumor microenvironments, such as hypoxia and low levels of nutrients, and play a role in upregulation of Nogo‐B in tumor angiogenesis. Abstract : Our results indicated that, although Nogo‐B played a complementary and parallel role in tumor angiogenesis to that of vascular endothelial growth factor, they shared a common induction mechanism of hypoxia inducible factor‐1 and activator protein‐1 activation, which might provide novel treatment options in hepatocellular carcinoma.